北大西洋涛动变率研究进展 - 龚道溢; 周天军; 王绍武 (地球科学进展, 2001)
介绍了近年来北大西洋涛动研究的最新进展。NAO指数序列的建立取得了很多成果，包括一些观测气象记录的序列以及利用树木年轮、冰芯等代用资料建立的近300多年的序列，这些长的序列显示NAO不仅有突出的年际变率，也有显著的年代际变率。总结了NAO对地面温度、降水、北大西洋飓风和北半球臭氧等影响的一些研究成果。NAO的低频变率可能与气候系统内部的相互作用以及外部强迫有关。许多模拟研究发现NAO与温盐环流有密切的联系，但是这种关系还有待观测资料的证实。全球气候变暖也可能是影响NAO变率的一个不可忽视的因素。 The recent advances in the studies on the North Atlantic oscillation(NAO) are reviewed.Some long time series of NAO index are established using both the instrumental and proxy data.The instrumental series is now extended back to AD1825.Proxy NAO indices reconstructed using tree ring data and/or ice core now attract more attention.Multiple-proxy reconstruction is now widely accepted for the purpose to reduce the uncertainty regarding of the individual proxy.As long as about three centuries' proxy NAO indices provide good representation of variability in natural context.The impacts of NAO on the climate are now studied in more details and have been connected to Arctic oscillation (AO).NAO and AO are the two paradigms of one phenomenon.Some model studies confirm that the thermohaline circulation (THC) may plays very important role in the low frequency of NAO.Some other external forces such as ozone and greenhouse warming are also considered as potential contributor to the observed recent trends in NAO. 国家重点基础研究发展计划(973计划); 国家自然科学基金 中国科学引文数据库(CSCD) 0 3 413-420 16